2003
DOI: 10.1046/j.1365-3059.2003.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative significance of nursery infections and orchard inoculum in the development and spread of apple canker (Nectria galligena) in young orchards

Abstract: Three nurseries produced apple rootstocks (M9) and budwood (cv. Royal Gala), which they exchanged at the end of the first year. Each nursery then budded its own budwood onto the rootstocks it had produced and that from the other two nurseries. Budded trees were grown on for a further year before being planted at HRI, East Malling in southern England; NIHPBS, Loughgall in Northern Ireland; and ADAS, Rosemaund in the West Midlands of England. Canker development was monitored twice a year. The position of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 8 publications
1
58
1
4
Order By: Relevance
“…The larger the wound and the higher the number of spores reaching the wound, the shorter the latent period from infection to symptom expression (Amponsah et al 2015;Walter et al 2016). Depending on wound size and spore load, a latency period as brief as 2-4 months is common (Walter et al 2016;Amponsah et al 2015); however, latent periods greater than three years have been reported (McCracken et al 2003). Inoculum control is a very important aspect in European canker disease control.…”
Section: Introductionmentioning
confidence: 99%
“…The larger the wound and the higher the number of spores reaching the wound, the shorter the latent period from infection to symptom expression (Amponsah et al 2015;Walter et al 2016). Depending on wound size and spore load, a latency period as brief as 2-4 months is common (Walter et al 2016;Amponsah et al 2015); however, latent periods greater than three years have been reported (McCracken et al 2003). Inoculum control is a very important aspect in European canker disease control.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the major source of infection by N. ditissima in newly planted orchards was brought in with the introduction of trees from nurseries, because significant numbers of young trees developed large cankers along the main stem. Since the trees did not show symptoms at the time of planting in the orchards, they likely became infected during propagation without showing symptom development (Brown et al 1994;McCracken et al 2003;Weber 2014). Several molecular tools have been developed to detect N. ditissima (Langrell and Barbara 2001;Langrell 2002;Ghasemkhani et al 2016).…”
mentioning
confidence: 99%
“…Latent infections are also reported for N. ditissima [32][33][34] and the latent period varies with wound size and spore concentration. Larger wounds and higher spore concentration shorten the latent period.…”
Section: Discussionmentioning
confidence: 98%
“…Latent natural infections are widely reported in literature where N. fuckeliana has been isolated from wounded and healthy looking stems of Norway spruce [5,12,13,35]. Furthermore, a light rain occurred during part of the inoculation process and the temperature was under 20 • C. Mild and wet weather conditions are favorable for pathogen sporulation, dispersal, and infection of N. ditissima [33,36,37] and likely also for N. fuckeliana. If the trees in the field trial received the same background inoculum level, then the larger lesion length under bark (approximately 12 mm or 46%) for the inoculated trees was likely due to the additional inoculum of N. fuckeliana mycelial plugs.…”
Section: Discussionmentioning
confidence: 99%